2016
DOI: 10.1016/j.hsag.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women living with borderline personality disorder

Abstract: There is limited understanding of the experiences of women living with borderline personality disorder. It was therefore decided to discover how women living with this disorder would tell their life story. For the researcher, who worked in a psychotherapy ward where most women were living with borderline personality disorder, the care of these women was of vital importance, as they were less understood by mental health care providers.The research aimed to explore and describe the experiences of women living wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Patients with BPD have been found to more frequently report childhood abuse or other traumatic events than individuals with other personality disorders or healthy individuals (APA, , ; Ntshingila, Poggenpoel, Myburgh, & Temane, ; Perry, Herman, Vanderkolk, & Hoke, ; Zanarini et al ., ). These self‐reported negative and often traumatic childhood experiences have been linked to impairments in the abilities to ‘mentalize’ (e.g., Bateman & Fonagy, ; Brüne, Walden, Edel, & Dimaggio, ; Fonagy & Bateman, ; Petersen, Brakoulias, & Langdon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with BPD have been found to more frequently report childhood abuse or other traumatic events than individuals with other personality disorders or healthy individuals (APA, , ; Ntshingila, Poggenpoel, Myburgh, & Temane, ; Perry, Herman, Vanderkolk, & Hoke, ; Zanarini et al ., ). These self‐reported negative and often traumatic childhood experiences have been linked to impairments in the abilities to ‘mentalize’ (e.g., Bateman & Fonagy, ; Brüne, Walden, Edel, & Dimaggio, ; Fonagy & Bateman, ; Petersen, Brakoulias, & Langdon, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of a prospective longitudinal study conducted with a large sample (consisting of 6,050 mothers and their children), it was found that the risk of developing BPD in children increases when there is hostility, resentment, and hitting/yelling by the first objects of the individual, and more conflict between parents, c (Winsper et al 2012). Borderline patients are exposed to the instability of their first object during childhood; this causes them to be deprived of adequate attention, care, and support (Bland et al 2007) and not know how to manage their emotions (Ntshingila 2016).…”
Section: Discussionmentioning
confidence: 99%
“…BPD patients state 9 Psikiyatride Güncel Yaklaşımlar-Current Approaches in Psychiatry that their first object is far from emotional warmth (Ghiassi et al 2010, Arens et al 2011, Huang et al 2014. From the findings obtained as a result of interviews with women diagnosed with BPD, it is seen that childhood is experienced in an unsafe area related to unhealthy family dynamics, boundary violations and educational and this creates a chronic feeling emptiness in individuals (Ntshingila 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, emptiness is often understood as a product of unstable object relations [83,[95][96][97][98], a split self [84,96,99], a false self [100], or absent identity [101,102]. In qualitative and quantitative work, emptiness has been linked to distorted self-image and lack of identity [103], identity diffusion [104], and general deficits in identity [79]. Some have theorized that boredom may also be related to identity disturbance [77], but there has been limited empirical consideration of this association.…”
Section: Boredom and Emptinessmentioning
confidence: 99%